2015
DOI: 10.1210/en.2015-1040
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Prolactin Regulation of Luteinizing Hormone Secretion in the Female Rat

Abstract: Prolactin (PRL) levels increase in response to long-term antipsychotic treatment that disrupts reproductive function. Recent evidence suggests that activation of central PRL receptors (PRLR) inhibits LH secretion and in ovariectomized rats. However, the mechanisms involved, the mode of LH secretion affected and relevance to hyperprolactinemia remain unknown. We therefore investigated the contribution of central PRL/PRLR signaling to the control of estradiol-induced surges of LH and PRL and pulsatile LH secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 118 publications
(104 reference statements)
1
10
0
Order By: Relevance
“…They also reported activation of central prolactin receptor which suppresses LH surge through GABA/GABAAR signaling. These observations could explain the previous reports on the role of prolactin in modulating hypothalamic role in regulating mammalian reproduction (34).…”
Section: Discussionsupporting
confidence: 84%
“…They also reported activation of central prolactin receptor which suppresses LH surge through GABA/GABAAR signaling. These observations could explain the previous reports on the role of prolactin in modulating hypothalamic role in regulating mammalian reproduction (34).…”
Section: Discussionsupporting
confidence: 84%
“…Female mice with deletions of PRL receptors are infertile because of failure in luteal function and embryo implantation . On the other hand, hyperprolactinaemia is a prevalent cause of infertility in both males and females . PRL secretion is tonically inhibited by dopamine released in the ME, mainly produced by the tuberoinfundibular dopaminergic (TIDA) neurones located in the ARC .…”
mentioning
confidence: 99%
“…Our study showed that GABA-T was mainly distributed in the adenohypophysis and Abat mRNA expression gradually decreased from infancy to 28 d, increased during the puberty stage, and decreased again in adulthood. Previous studies have shown that GABA can inhibit the secretion of LH and PRL through the dopamine system and the addition of GABA-T inhibitors in vitro and in vivo results in a decrease in PRL release from the pituitary [15,19,48,49]. PRL regulates the reproductive axis by acting on hypothalamic neurons expressing the Kiss1 gene [50,51], indicating that GABA-T regulates the release of pituitary hormones (LH and PRL) via the GABAergic system, thus affecting the reproductive axis.…”
Section: Discussionmentioning
confidence: 99%
“…GABA functions keep the brain strong, and it has anti-anxiety, analgesic, hypnotic and forgetting effects [13,14]. Recent studies have shown that GABA inhibits the secration of luteinizing hormone (LH) and prolactin (PRL) in the anterior pituitary gland [15], and GABA has been found in more than 30 peripheral tissues, including ovarian and fallopian tubes [16]. Other studies have shown that GABA receptors (GABAA and GABAB) can stop the sperm acrosome reaction [17] and GABA regulates follicular development and pregnancy [16].…”
Section: Introductionmentioning
confidence: 99%